Tren Penerapan Model Kooperatif Tipe Think Pair Share (TPS) Dalam Pembelajaran Matematika: Systematic Literature Review - Fitriani, Elia; Sukasno; Drajat Friansah (STAI Al-Bahjah, 2024)
Teachers must use appropriate learning models, if the learning models used are not appropriate, students will experience difficulties in learning and this will result in low student learning outcomes. Researchers aim to determine trends in the application of the Think Pair Share type cooperative learning model in mathematics learning. The method used by researchers is Systematic Literature Review. Researchers used articles consisting of 12 inclusion articles and 10 exclusion articles for a total of 22 articles. Based on the results of the researcher's review of the article (Agustina, 2021), the increase in student learning outcomes occurred because there were interaction activities between teachers and students which were implemented through the Think Pair Share type cooperative model. According to (Izzah & Qohar, 2020) the application of the Think Pair Share type cooperative model can improve understanding of algebra concepts, according to (Hartini, Maharani & Rahman, 2016) The application of the Think-Pair-Share Learning Model can improve Mathematical Communication Skills, so researchers can conclude that Think Pair Share type cooperative learning model in mathematics learning can solve various problems such as improving student learning outcomes, increasing learning achievement, can improve concept understanding abilities, improve mathematical problem solving abilities, improve communication skills students' mathematics and critical thinking.